The strategic challenges of under armour in 2021 with an analysis of the firm in China - Casanova, Rodrigo Rijo (2022)
This work project describes Under Armour’s efforts to create and sustain superior value in the global sportswear market. It is intended to be used in masters and executive education Strategy courses. Following the guidelines of the field lab, a case study about the market situation and the firm is presented. We proceed with a literature review to discuss theoretical concepts. This is followed by an analysis, where the theory is applied to the case of Under Armour. A focus will be placed on the firm’s international presence, mainly in China. Exclusively secondary sources were used.